Assessment on The Use of Youtube, Instagram and Tiktok Affect Study Habit and Academic Performance Among Undergraduates Students of Abubakar Tafawa Balewa University, Bauchi - Kayode Sunday John Dada; Yunana Gladys MUSA (Journal in Teaching and Education Area, 2026)
This study examined the use of YouTube, Instagram, and TikTok  affect study habit and academic performance among undergraduate students of Abubakar Tafawa Balewa University (ATBU), Bauchi. The study adopted the survey method using a structured questionnaire administered through Google Forms. A total of 387 responses were collected and analyzed using bar and pie charts to represent demographic data and patterns of usage. Findings revealed that while all three platforms are actively used, YouTube emerged as the most preferred, especially for educational and informational purposes. Instagram and TikTok were more associated with entertainment and social interaction. However, YouTube showed the most positive influence on academic performance, whereas Instagram and TikTok were more likely to cause distractions. The study concludes that students of ATBU, Bauchi utilized each platform to satisfy different needs ranging from learning and relaxation to self-expression and trend participation. The study recommends that students adopt more intentional use of social media, especially platforms like YouTube, to support academic goals, while being mindful of the distractions that may arise from overuse of entertainment-based platforms.